THE KEY FACTORS INFLUENCING CONSUMER BEHAVIOR TOWARDS GREEN COSMETICS, INCLUDING PRODUCT ATTRIBUTES, BRAND REPUTATION, AND SUSTAINABILITY INITIATIVES - Choudhary, Aavishka; Singh, Ajeet (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The increasing awareness of environmental sustainability has resulted in a rise in the demand for eco-friendly cosmetics. This research seeks to investigate the main aspects that affect how consumers behave when it comes to green cosmetics. It will pay special attention to product features, brand reputation, and sustainability activities. This study aims to identify the main factors that influence decision-making in the green cosmetics industry by examining the preferences and buying habits of consumers. The results will provide useful information for companies, legislators, and marketers that are working to improve sustainability practices and create a customer base that is more aware of environmental issues. The research uses a mixed-methods technique, which includes surveys and data analysis, to determine the importance of different factors. The findings provide a better understanding of why consumers make the choices they do, which helps firms create successful strategies to promote environmentally responsible goods while still satisfying customer expectations.